Amanah Metaphor in Medical Waste Prevention Effects Environmental Cost Accounting - Muhammad Wahyuddin Abdullah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
This study aims to determine the application of environmental cost accounting in Islamic Hospitals which is framed in the concept of the metaphor of Amanah as an effort to prevent medical waste that can damage the environment. The object of this research is the Faisal Islamic Hospital in Makassar. This study is qualitative approach with a case study approach. The results showed that Faisal Islamic Hospital has maintained and maintained the environment in accordance with Standard Operating Procedures (SPO). Faisal Islamic Hospital has implemented environmental cost accounting which includes identification, recognition, measurement, presentation, and disclosure. The policies implemented by the hospital are a form of vertical accountability to Allah swt and horizontal accountability to humans and the environment. The theoretical and practical benefits of this research are as material for further research that can be developed by their respective ideas and creativity and can be used as material for hospital considerations regarding the application of Environmental Cost Accounting as a form of social responsibility towards the environment, especially in terms of hospital waste management.